In vivo measurements of blood vessels' distribution in non‐melanoma skin cancer by dynamic optical coherence tomography — a new quantitative measure?. Issue 1 (3rd August 2017) - Sigsgaard, V.; Themstrup, L.; Theut Riis, P.; Olsen, J.; Jemec, G. B.
Abstract: Background: Skin biopsies only provide point‐in‐time data making longitudinal studies difficult. Using Dynamic optical coherence tomography (D‐OCT) in vivo, non‐invasive imaging of the microvasculature becomes possible. The current OCT literature is almost exclusively based on qualitative information but quantitative data may offer additional advantages, for example, by reducing observer variation. The objective of this study was to evaluate the in vivo superficial distribution of blood vessels, defined as the surface‐to‐first‐vessel distance, in actinic keratosis, basal cell carcinoma, squamous cell carcinoma and normal skin. Methods: D‐OCT images of 52 histologically verified lesions and corresponding normal skin were included. The dataset consisted of 13 AK, 22 BCC and 17 SCC. No tumour sub‐classification was done. Results: The quantitative measurement of the surface‐to‐first‐vessel distance showed a significant difference between NMSC and corresponding normal skin. Significant differences were also seen for BCC, and it is hypothesized that the measure may also be able to distinguish between AK and SCC (borderline significant differences). Conclusion: Our results could prove useful in discriminating between non‐melanoma skin cancer lesions and healthy skin and in making a specific diagnosis. It is suggested that collecting different quantitative measurements increases the utility of D–OCT and makes the method less observer‐dependent.